2005
DOI: 10.1177/0145482x0509900805
|View full text |Cite
|
Sign up to set email alerts
|

Self-evaluation and Recruitment of Feedback for Enhanced Social Interaction by a Student with Visual Impairment

Abstract: A student who is visually impaired was trained to evaluate his social behavior and to recruit feedback from his sighted peers, who were trained by him to provide the feedback. The self-recruitment of feedback improved the student's accuracy in evaluating social skills requiring visual cues. In addition, the peers extended their feedback to other aspects of the social environment than social behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 9 publications
3
13
0
Order By: Relevance
“…In a case study, Celeste (2007) found that the number of interactions and the play behaviours of a preschooler with visual impairments increased following her participation in an intervention comprising social skills training and activities for the girl and her peers. Similar results are reported by Jindal-Snape (2005a, 2005b: self-evaluation and the social skills of two boys with visual impairments improved after an intervention in which sighted peers provided feedback to them. Finally, Peavey and Leff (2002) demonstrated that the implementation of an intervention aiming to enhance the understanding of diversity contributed to the improvement of social skills and social acceptance levels of children with visual impairments.…”
Section: The Outcomes Of Educational Interventions On the Academic Lesupporting
confidence: 80%
See 1 more Smart Citation
“…In a case study, Celeste (2007) found that the number of interactions and the play behaviours of a preschooler with visual impairments increased following her participation in an intervention comprising social skills training and activities for the girl and her peers. Similar results are reported by Jindal-Snape (2005a, 2005b: self-evaluation and the social skills of two boys with visual impairments improved after an intervention in which sighted peers provided feedback to them. Finally, Peavey and Leff (2002) demonstrated that the implementation of an intervention aiming to enhance the understanding of diversity contributed to the improvement of social skills and social acceptance levels of children with visual impairments.…”
Section: The Outcomes Of Educational Interventions On the Academic Lesupporting
confidence: 80%
“…Five studies investigated the outcomes of educational interventions in which both students with and without visual impairments participated. The interventions took place in mainstream schools and aimed to increase social interactions and communication (Celeste, 2007;D'Allura, 2002;Jindal-Snape, 2005a, 2005bPeavey & Leff, 2002). D'Allura (2002) found that the use of a cooperative learning strategy in an integrated class contributed to an increase in the length of interactions among preschoolers with and without visual impairments.…”
Section: The Outcomes Of Educational Interventions On the Academic Lementioning
confidence: 99%
“…D' Allura (2002) found increased social interaction in preschool students through cooperative learning strategies and integration of sighted peers into special education classes. Finally, Jindal-Snape and colleagues have used self-evaluation and peer feedback interventions to increase social interaction skills in children with visual impairments (Jindal-Snape, 2004, 2005a, 2005bJindal-Snape, Kato, & Maekawa, 1998).…”
Section: Social Skills Interventions In Children With Visual Impairmentsmentioning
confidence: 99%
“…Blindness research on the relational level is pretty much done. However, such studies involving children, such as communication patterns (Herrera, 2015;Cascella, Trief, & Bruce, 2012), social interaction (Celeste, 2006;Jindal-Snape, 2005a, 2005b, and interpersonal competence (Ayomi, 2009). There is also a study of visual impairment people teenager, who studies courtship (Fichten, Goodrick, Amsel, & McKenzie, 1991;Murniasih, 2004), social interaction between persons with visual impairment (Meriyani, 2013), and comparative orientation of the friendship between the visual impairments since birth with a group of visual impairment people who've seen (Herlina et al, 2008).…”
Section: Introductionmentioning
confidence: 99%